Intraoperative Injection of Normal Saline Through Lumbar Drainage for Transnasal Endoscopic Repair of Complex CSF Leaks - Wei, Xiaoming; Zhang, Fan; Qiu, Yankai; Shen, Hong; Ilyasova, Tatiana; Liu, Li (Frontiers in Surgery, 2022)
Objective It is well known that accurate location of the leak in the operation is crucial for repairing cerebrospinal fluid leakage. The study aims to investigate the application of intraoperative injection of normal saline through lumbar drainage in repairing complex leaks. Methods The fistulas of all patients with CSF leak were located by computed tomography cisternography (CTC) or heavy T2 magnetic resonance imaging (MRI) before surgery. Before anesthesia, the patient underwent lumbar drainage implantation, and then 20 ml of normal saline was slowly injected through the lumbar drainage to observe the patient's response. The surgical approach was designed based on the preoperative imaging data. When the operation was near to the suspected fistula, normal saline was injected through lumbar drainage (20 ml each time) to confirm the leak location. After CSF leak repair, saline was injected again to confirm whether the repair was successfully. Result Of the 5 patients with complex leaks, 4 cases were repaired by transnasal endoscopy method, and 1 case was repaired by transnasal endoscopy method and epidural method. A total of 7 leaks were found during the operation. During the operation, 40–120 ml of normal saline was injected through lumbar drainage. Cauda equina neuralgia was developed in patients who received 120 ml normal saline, which was relieved by intrathecal injection of dexamethasone. During the follow-up of 3 months, 1 case suffered from brain abscess, which was controlled by vancomycin. There was no recurrence of rhinorrhea. Conclusion Intraoperative injection of normal saline through lumbar drainage can not only better expose the complex leak but also check the repair effect of the leak during transnasal endoscopic repair, which is effective and avoids side effects.